2001
DOI: 10.1021/jp003585s
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Carbon Monoxide Adsorption on Pt(111) Revisited:  A Sum Frequency Generation Study

Abstract: The adsorption of CO on Pt(111) was studied by picosecond infrared-visible sum frequency generation (SFG) vibrational spectroscopy in a pressure range from 10 -7 to 500 mbar and in a temperature range of 160-400 K. At low pressure the experiments were complemented by TPD, LEED, and AES. Terminally bonded (on-top) CO was the only species observed between 160 and 400 K, independent of gas pressure. The CO stretching frequency was blue-shifted by about 15 cm -1 with increasing pressure (up to 2097 cm -1 ), but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
143
1
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(156 citation statements)
references
References 39 publications
8
143
1
3
Order By: Relevance
“…2a suggests that for ambient partial pressures at room temperature (and even higher), the c(4 · 2)-2CO overlayer forms on the metallic part of the Pt surface. This structure is the well-characterized low-pressure, room-temperature equilibrium structure [5] of CO at Pt (1 1 1). The GGA-PW91 based phase diagram depicted in Fig.…”
Section: Structure Of Three-phase Boundarymentioning
confidence: 69%
See 1 more Smart Citation
“…2a suggests that for ambient partial pressures at room temperature (and even higher), the c(4 · 2)-2CO overlayer forms on the metallic part of the Pt surface. This structure is the well-characterized low-pressure, room-temperature equilibrium structure [5] of CO at Pt (1 1 1). The GGA-PW91 based phase diagram depicted in Fig.…”
Section: Structure Of Three-phase Boundarymentioning
confidence: 69%
“…The application of in situ experimental techniques, including high-pressure scanning tunneling microscopy [1,2], X-ray diffraction [3], sum frequency generation [4,5], and high resolution transmission electron microscopy [6] have shown that catalytic surfaces often undergo structural transitions under reaction conditions. In the case of oxidation reactions at transition metal surfaces it has been suggested that high coverage oxygen chemisorption phases, surface oxide phases, or bulk oxide phases are the relevant reaction states of the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…It was generally believed that Pt does not appreciably dissociate CO, although controversial results were reported [5][6][7][8][13][14][15][16]. Somorjai and co-workers first showed that CO dissociation on Pt is, in fact, a surface structure sensitive reaction [13].…”
Section: Introductionmentioning
confidence: 99%
“…Using sum frequency generation spectroscopy at 40 Torr of CO and Auger electron spectroscopy (AES) McCrea et al showed that CO dissociation occurs on Pt(111), Pt(557) and Pt(100) at 673, 548 and 500 K, respectively [17]. The authors suggested that dissociation proceeds via CO-induced surface roughening at high pressures and temperatures, but this mechanism was revisited in the more recent work by Rupprechter et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…This complex behavior was contradicted by a more recent study by Freund and coworkers. 61 After correcting the data for the gas-phase IR absorption, the peak ascribed to CO adsorbed on atop sites was found not to be suppressed. In fact, it increased in intensity corresponding to a coverage of B0.…”
mentioning
confidence: 97%